'妈妈, I miss you ': Emotional multilingual practices in transnational families. (April 2023) - Curdt-Christiansen, Xiao Lan; Iwaniec, Janina
Aims: This study explores how home language(s) are used in bilingual family members' daily digital or non-digital interactions to demonstrate their emotions and affections for each other. The study investigates linguistic features and situated-language use of home language(s) in emotional negotiations between family members. In addition, it explores how multimodalities and languages are mixed to contribute to the interactional dynamics underlying 'family talk' and how children and adults position themselves emotionally in moment-to-moment interaction of family life. Methodology: This study involves six families from two transnational communities (Chinese and Polish) and it employs an ethnographic research design for data collection. Data and analysis: Data sources include recordings of mealtime conversations, daily WhatsApp/WeChat texts, and digital-mediated family talk recorded by the families themselves. Affective repertoire is used as an analytical framework. Findings and conclusions: The following five key features are identified in online or offline family talks regarding expression of emotionality: emojis, terms of endearment, diminutives, declaration of love and situated emotive language use. Originality: Unlike recent studies of emotions in bi-multilingual families, this study does not rely on surveys, memoirs, or interviews. Few studies have investigated how family members present their emotional expression in their daily communications, what role home/heritage language(s) actually play in communicating their emotional needs, and how these emotional expressions are manifested in their lived experiences and socialisation practices. Significance and implications: The findings contribute to FLP literature by looking into how emotions are involved in the practices of family life and the construction of familyness. Emotions, as a key factor in FLP, are directly related to parents' perceptions of and investment in their heritage language. Although these perceptions are linked to the powerful societal languages that often represent educational possibilities, when it comes to emotional expressions, the primacy is given to the first language/heritage language.